Uji Efikasi Herbisida Isopropil Amina Glifosat, Triklopir, Glufosinat dalam Mengendalikan Gulma Psychotria serpens di Perkebunan Kelapa Sawit - Tarigan, Rio Ganda Terkelin; Tarmadja, Samsuri; Yuniasih, Betti (Program Studi Agroteknologi INSTIPER, 2025)
Oil palm productivity is affected by many factors, one of which is weeds that can cause the oil palm productivity to not be maximized. Psychotria serpens is an example of a weed in oil palm plantations. This weed grows creeping in the circle and path so it disrupts oil palm management. This study was conducted to determine the effectiveness of isopropyl amine glyphosate, triclopyr and glufosinate herbicides in controlling Psychotria serpens weeds in oil palm plantations. This research was conducted at PT. Bahana Karya Semesta, Sungai Mentawak Estate, Air Hitam District, Sarolangun Regency, Jambi from March to April 2023. The study used a factorial experiment consisting of 2 factors and arranged in a completely randomized design with 3 replications. The first factor was the type of active ingredient consisting of isopropyl amine glyphosate, triclopyr, and glufosinate, the second factor is the dose of herbicide formulation which is 0.15ml/m2, 0.30ml/m2, 0.45ml/m2, and 0.6ml/m2. Observations were made for 5 weeks. The results of observations were analyzed using oneway anova which was further tested using DMRT 5%. The results was Glyphosate and Glufosinate at all formulation doses could not control Psychotria serpens. Triclopyr at formulation doses 0.15ml/m2 and 0.30ml/m2 was not able to control Psychotria serpens, and at formulation doses 0.45ml/m2 and 0.6ml/m2 showed death in Psychotria serpens. Based on the results of the study, it can be concluded that the best type of active ingredient in controlling Psychotria serpens weeds was the active ingredient Triclopyr with a formulation dose 0.45ml/m2.